2005
DOI: 10.1179/174329405x50091
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and electrophoretic deposition of hydroxyapatite for orthopaedic applications

Abstract: The basic calcium phosphate mineral, hydroxyapatite (HAP) (Ca 10 (PO 4 ) 6 (OH) 2 ), is the prototype of one of the major constituents of bone and teeth. Thin layers of HAP were coated on the surface of type 316L stainless steel by electrophoretic deposition (EPD) from a 2 . 5% suspension in isopropyl alcohol, and this was followed by vacuum sintering at 800uC for 1 h. The development of HAP coatings was affected by the applied potential and time. In addition, HAP coatings were synthesised on pure Ti by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 11 publications
3
61
1
2
Order By: Relevance
“…It has been reported that highly crystalline structures make less soluble coatings [8]. So the high crystallinity of the coating may decrease the biodegradation rate.…”
Section: mentioning
confidence: 99%
“…It has been reported that highly crystalline structures make less soluble coatings [8]. So the high crystallinity of the coating may decrease the biodegradation rate.…”
Section: mentioning
confidence: 99%
“…Compared toAR-316, the OCP of HA/CNT-316 shifted towards noble direction and reached a potential of -150 mV (increased by 110 mV). Similar behavior where the OCP of 316L increases after coated with HA has been reported byEliaz et al [11]. The present resultsshow that thermodynamic stabilityof the HA/CNT-316 in 0.9% NaCl solutionat 37 P o PC.…”
Section: Methodssupporting
confidence: 91%
“…Furthermore, multi-walled carbon nanotubes can be functionalized by deposition of calcium orthophosphate coatings [536]. The list of most important coating techniques is comprised in Table 5, while the main advantages and drawbacks of each coating technique, as well as the major properties of the deposed calcium orthophosphates, are discussed in details elsewhere [194,240,295,525,526,[537][538][539][540][541][542][543][544][545][546][547][548][549][550][551]. Unfortunately, none of these methods is able to provide the perfect covering because each coating always contains cracks, pores, second phases and residual stresses that reduced their durability and might lead to a partial or complete disintegration of the coating in body fluids.…”
Section: Coatingsmentioning
confidence: 99%